Development, Estimation And Validation Of Bosentan In Bulk And In Its Pharmaceutical Formulation By UV-Vis Spectroscopic Method - A.ASHOK KUMAR; A.ANIL KUMAR; D.GOURI SANKAR (International Journal of Pharma and Bio Sciences, 2011)
method for the determination of bosentan present in pharmaceutical dosage forms. The method is validated for the determination of bosentan in bulk and tablet dosage form. Bosentan is a dual endothelin receptor antagonist used in the treatment of pulmonary artery hypertension (PAH). The solvent used was methanol: water (60:40) and the λmax or the absorption maxima of the drug was found to be 270nm. A linear response was observed in the range of 10-90μg/ml with a regression coefficient of 0.9993. The method was then validated for different parameters as per the ICH (International Conference for Harmonization) guidelines. This method can be used for the determination of Bosentan in quality control of formulation without interference of the excipients.